A/r/tographic inquiry in sport and exercise research: a pilot study examining methodology versatility, feasibility and participatory opportunities. Issue 4 (8th August 2017) - McMahon, Jenny; MacDonald, Abbey; Owton, Helen
Abstract: This research paper centres on a pilot study where a/r/tography, an arts-based methodology, was implemented into a sport and exercise research context. A/r/tography is yet to be employed in this particular research context; therefore, an emphasis is placed on exploring the versatility and feasibility of this methodology when applied to the field of sport and exercise. In addition, we explore whether a/r/tography offers anything new and/or unique in comparison to other arts-based research that has already been conducted in this domain. In the paper that follows, we outline what a/r/tography is; why it could be considered as a methodological approach in sport and exercise research; and how it has been used in other research domains such as the social sciences. The remainder of the paper is dedicated to outlining the method that was undertaken in the a/r/tographic inquiry. A/r/tography was implemented with one swimmer participant and focused on the 'normalised' yet destructive 'slim to win' body practices found to be occurring in swimming culture. Four interrelated parts of the a/r/tographic inquiry process are highlighted so other sociocultural sport researchers can understand how to implement the approach. The feasibility and educative outcomes of the methodology are also discussed. The final section of the paper outlines the learning outcomes for the swimmer participant after engaging with the a/r/tographic inquiry process. A critical discussion is also presented outlining whether a/r/tography offers anything new than other arts-based research.